Since acceleration is constant, the average and instantaneous accelerations are the same, so that
![a = a_(\rm ave) = (\Delta v)/(\Delta t) = -(v_i)/(10.0\,\rm s)](https://img.qammunity.org/2023/formulas/physics/high-school/oobps9pbvrg8wb72tu950d304doqsh6b1v.png)
By the same token, we have the kinematic relation
![v^2 - {v_i}^2 = 2a\Delta x](https://img.qammunity.org/2023/formulas/physics/high-school/petfztl19c428sxvdhvdtssa5aj674kcdw.png)
where
is final speed,
is initial speed,
is acceleration, and
is displacement.
Substitute everything you know and solve for
:
![0^2 - {v_i}^2 = 2\left(-(v_i)/(10.0\,\rm s)\right)(75.0\,\mathrm m)](https://img.qammunity.org/2023/formulas/physics/high-school/dnrahulizpqdbkf2ofhr3jofysucu6s9rb.png)
![\implies {v_i}^2 - \left(15.0(\rm m)/(\rm s)\right) v_i = 0](https://img.qammunity.org/2023/formulas/physics/high-school/wcwikvlun7uygsahephvwmhm1clgig7y1i.png)
![\implies v_i \left(v_i - 15.0(\rm m)/(\rm s)\right) = 0](https://img.qammunity.org/2023/formulas/physics/high-school/kj51wo0nqha0qnzzk6af6jvknx3xr0o9jx.png)
![\implies v_i = \boxed{15.0(\rm m)/(\rm s)}](https://img.qammunity.org/2023/formulas/physics/high-school/sknc4rgxpeu01tjs1473thclg4hsc4o5xy.png)